If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
y-4 = (11/3)*(x-4) // - (11/3)*(x-4)
y-((11/3)*(x-4))-4 = 0
(-11/3)*(x-4)+y-4 = 0
y-11/3*(x-4)-4 = 0
y-11/3*(x-4)-4 = 0
y-11/3*x-4+44/3 = 0
y-11/3*x+32/3 = 0
y-11/3*x+32/3 = 0
y-11/3*x+32/3 = 0 // - y+32/3
-11/3*x = -(y+32/3) // : -11/3
x = (-(y+32/3))/(-11/3)
x = 3/11*(y+32/3)
x = 3/11*(y+32/3)
| 3+ln(x^2-1)=ln(x+1) | | Ln(x^2-1)+3=ln(x+1) | | 9s-1/3=32/3 | | 4z+4=5z-7 | | 5x^2+8=23 | | 1y+50=50 | | 35c+140=1050 | | 3*3.2=11 | | 3*3.6=11 | | AE=5x+13 | | x^2+x=412 | | BD=4x+2 | | 21y+9=89 | | 12x=15*16.88 | | x*(k+2)-x*(k+1)+x*(k)=g*(k) | | y=4cos(x)-3x^2-2 | | 2x+90+26=360 | | x+27=3x+1 | | 2x+5-12=14x+8 | | -7x-4y=9 | | 13(4-3)= | | 2x-4=3x-11 | | 117=.12x+x | | 2/3m-6.5=.7 | | 21x^4-6x^3+42x^2-12x=0 | | [5+(-2)]-4= | | j=y/q | | 18+[-6+(-5)]= | | 2x+3x=1459 | | (8-12)= | | (5x-8)(7x+7)=0 | | [(8-12)]+0= |